Pertanggungjawaban Notaris Atas Keterangan Palsu yang Disampaikan Penghadap Dalam Akta Pendirian Perseroan Terbatas - Amelia, Sandra (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Example of a problem involving a Notary in a legal dispute that arises in the case of establishing a limited liability company whose deed of establishment contains false information. The author of this research wants to study and analyze further the legal implications of a limited liability company deed made based on false information and the form of notary responsibility for a limited liability company deed based on false information. The research method used is normative legal research. The research results show that for the establishment of a limited liability company, a claim for revocation of the establishment can be filed in court if the founding agreement contains deed defects due to false statements. Cancel the contract establishing the limited liability company. In this case the Notary is not responsible for losses resulting from inaccurate information